Front Cover: High Open‐Circuit Voltage Cs2AgBiBr6 Carbon‐Based Perovskite Solar Cells via Green Processing of Ultrasonic Spray‐Coated Carbon Electrodes from Waste Tire Sources (ChemSusChem 22/2022). Issue 22 (4th November 2022) - Schmitz, Fabian; Lago, Nicolò; Fagiolari, Lucia; Burkhart, Julian; Cester, Andrea; Polo, Andrea; Prato, Mirko; Meneghesso, Gaudenzio; Gross, Silvia; Bella, Federico; Lamberti, Francesco; Gatti, Teresa
Abstract : The Front Cover shows the transformation of waste tires into a conductive carbon material that can be employed for the additive‐free preparation of hole‐extracting electrodes incorporated within lead‐free perovskite solar cells (an end‐of‐waste strategy). These highly sustainable and low‐cost photovoltaic devices will pave the way to the powering of the IoT ecosystem within households, when LED illumination is turned on. More information can be found in the Research Article by F. Schmitz, N. Lago, et al .